The Brazilian way of doing public administration : Brazil with an 's' - Lisboa, Erika; Gomes, Ricardo Corrêa; Martins, Humberto Falcão (Emerald Publishing Limited, 2023)
Brazil is a pioneer in the development of participation policies, with the most advanced banking systems in the world and a health system that serves the majority of a population scattered over more than 8.5 million square kilometres. However, Brazil also displays one of the highest rates of social and economic inequality worldwide, unable to fight illiteracy, school dropout, lack of basic sanitation, and unemployment. The Brazilian Way of Doing Public Administration is an accessible collaboration between scholars and practitioners rich with findings applicable worldwide, exploring Brazil's government's functioning at various points in recent history. Comprehensively presenting public management cases and theories in two sections - public management and public policy - the chapters provide scholars and practitioners with unique and previously underexplored insights and experiences. Exploring links between administrative systems and policy performance, The Brazilian Way of Doing Public Administration is a necessary book for practitioners, policymakers and researchers in management, public administration, business, and economics.